2016
DOI: 10.1111/ibi.12389
|View full text |Cite
|
Sign up to set email alerts
|

Mutual ornamentation and the parental behaviour of male and female Collared Flycatchers Ficedula albicollis during incubation

Abstract: One of the benefits of mate choice based on sexually selected traits is the greater investment of more ornamented individuals in parental care. The choosy individual can also adjust its parental investment to the sexual signals of its partner. Incubation is an important stage of avian reproduction, but the relationship between behaviour during incubation and mutual ornamentation is unclear. Studying a population of Collared Flycatchers Ficedula albicollis, we monitored the behaviour of both sexes during incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…, but see Martin & Wiebe , Kötél et al . ) and did not differ between yearling and older males or females (as reported in previous studies: Table S2). We also found no effect of extra‐pair paternity on a male's feeding behaviour during incubation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…, but see Martin & Wiebe , Kötél et al . ) and did not differ between yearling and older males or females (as reported in previous studies: Table S2). We also found no effect of extra‐pair paternity on a male's feeding behaviour during incubation.…”
Section: Discussionsupporting
confidence: 78%
“…, Kötél et al . ). Similarly, one could expect that a higher male incubation feeding rate enhances reproductive success.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship changes very little when omitting the lowest value of patch size change (HBA effect after omission, F 1,29 = 5.686, p = 0.024) In the nestling rearing stage, no measure of actual nutrition showed any correlation with badge sizes. In our population, despite some consistent relationships between nestling growth and male badge sizes (Szöllősi et al 2009;Hegyi et al 2011), no correlational or experimental study has shown any robust link between measures of male parental care and forehead or wing patch size (Kiss et al 2013;Kötél et al 2016;Laczi et al 2017). Therefore, nutritional reserve management in the nestling rearing period may indeed not be closely linked to ornamentation.…”
Section: Discussionmentioning
confidence: 59%
“…Actual reserve accumulation will correlate (uncertain sign) with current wing patch size in the courtship phase when this patch has major role as a territorial signal (Garamszegi et al 2006a) but such correlation is not expected for forehead patch size or in the nestling stage where male behaviour is not linked to patch sizes (Kiss et al 2013;Laczi et al 2017) 3. Reserve depletion will negatively correlate with current wing patch size during courtship if large-patched males suffer energetic shortcomings due to the territorial role of the trait (Garamszegi et al 2006a, b; see also Kötél et al 2016). 4.…”
Section: Introductionmentioning
confidence: 99%
“…The nestling period lasts for 14-16 days. The female incubates the eggs alone, while being fed by its partner (Kötél et al 2016), and both parents provision the nestlings.…”
Section: Study Species and Study Areamentioning
confidence: 99%